Analysis Of Parenting Patterns On School Children's Compliance In The Implementation Of Health Protocol In The Time Post Coronavirus Disease Pandemic 2019 In Sdn 4 Tosaren Kediri City - Eva Agustina Yalestyarini,; Beny Setiawan,; Dorkas Kali Ghoba, (Journal of Health Science Community, 2023)
The application of the 5M health protocol to children at SDN Tosaren 4 in the post-pandemic period requires parental parenting to familiarize children with complying with health protocols so that they are not infected with Covid-19. The purpose of this study was to determine the analysis of parenting patterns on school children's compliance in the application of the 5 m health protocol in the post-Coronavirus Disease 2019 pandemic.The research design used was quantitative research with an observation/survey research design with a cross-sectional approach, the sampling technique was purposive sampling. The population in this study are all parents who have school children, the sample is some parents who have school children. This study used a questionnaire to the child's parents and then carried out data processing with Spearman Rank Correlation.The results of the measurement of parenting patterns can be described that from 53 respondents there are mostly parents with good parenting as much as 48 or 90.6%. Based on the compliance that out of 53 respondents, most of the children obeyed as much as 44 or 83%. the results of the analysis test obtained a correlation coefficient of 0.714, meaning that the level of strength of a strong relationship between the variables of parenting and compliance. The significance value is 0.000. so that parenting with obedience has a relationship. Parental Parenting Patterns on School Children's Compliance in the Implementation of the 5 M Health Protocol in the Post-Coronavirus Disease 2019 Pandemic at SDN Tosaren 4, Kediri City. Good parenting patterns regarding the application of health protocols in the post-Covid-19 period will have an impact on children's adherence to healthy behavior. So that children who comply with health protocols can avoid the transmission of COVID-19.